A Possible Resolution to Troubles of SU(2) Center Vortex Detection in Smooth Lattice Configurations - Rudolf Golubich; Manfried Faber (Universe, 2021)
The center vortex model of quantum-chromodynamics can explain confinement and chiral symmetry breaking. We present a possible resolution for problems of the vortex detection in smooth configurations and discuss improvements for the detection of center vortices.